Critical thinking in nursing: Scoping review of the literature. Issue 6 (12th May 2014) - Zuriguel Pérez, Esperanza; Lluch Canut, Maria Teresa; Falcó Pegueroles, Anna; Puig Llobet, Montserrat; Moreno Arroyo, Carmen; Roldán Merino, Juan
Abstract : This article seeks to analyse the current state of scientific knowledge concerning critical thinking in nursing. The methodology used consisted of a scoping review of the main scientific databases using an applied search strategy. A total of 1518 studies published from January 1999 to June 2013 were identified, of which 90 met the inclusion criteria. The main conclusion drawn is that critical thinking in nursing is experiencing a growing interest in the study of both its concepts and its dimensions, as well as in the development of training strategies to further its development among both students and professionals. Furthermore, the analysis reveals that critical thinking has been investigated principally in the university setting, independent of conceptual models, with a variety of instruments used for its measurement. We recommend (i) the investigation of critical thinking among working professionals, (ii) the designing of evaluative instruments linked to conceptual models and (iii) the identification of strategies to promote critical thinking in the context of providing nursing care.